Time dependent behavior of a FRR thermal break pad under compressive loads. (June 2015) - Oostdyk, Matthew; Polhemus, Matthew; Gabrielsen, Andreas; Cleary, Douglas B.; Riddell, William T.
Abstract: Fiber reinforced resin plates are used to provide thermal breaks where structural supports penetrate the building envelope. Tests were performed to evaluate the influence of these thermal plates on time-dependent load loss under compressive loading in bolted connections. Configurations considered included a base case without thermal barrier material, configurations with a 25.4 mm thermal barrier plate, and configurations with a steel plate of the same thickness as the thermal barrier. Additional cases also included thermal barrier material washers and two different size cover washers. The bolts in the connections were tightened to approximately 15% over the minimum specified pretension and then monitored for up to 1000 h. The total loss of clamping force measured from the sum of the initial tensioning force until a stable force was achieved were approximately the same for the base configuration all-steel connection and the configurations with thermal barrier, thermal washers and larger diameter hardened washers. Inclusion of the thermal washer resulted in load losses between initial tightening and stabilization that were larger than found in the baseline all-steel assemblages, and larger than found when a 25.4 mm steel or 25.4 mm thermal barrier plate was included.